The Tendency to Commit Violence in Dating Seen from Emotional Regulation - Firmansyah, Hendra; Mubina, Nuram; Leometa, Citra Hati (Philanthropy: Journal of Psychology, 2025)
Violence is a growing problem among adolescents and young adults, particularly in the Karawang region. This study aims to analyze the influence of emotion regulation on the tendency to perpetrate dating violence among university students in Karawang. A causal-associative quantitative method was employed, utilizing a sample of 100 students aged 18-29 years selected through convenience sampling. Data analysis was performed using simple regression with the aid of IBM SPSS Statistics 25. The results indicate a significant negative correlation between emotion regulation and dating violence (p=0.000<0.01), with a coefficient of determination (R2) of 49.1%. This suggests that nearly half of the variability in dating violence is influenced by individuals' ability to regulate their emotions. These findings imply the necessity of developing psychological interventions that focus on enhancing emotion regulation as a primary strategy in the prevention and management of violence in dating relationships.